Approaches to empirical research on inclusive education - Peder Haug (Scandinavian Journal of Disability Research, 2010)
Empirical and critical studies of inclusion and inclusive practices in school represent different understandings of inclusion and different approaches to studying the phenomenon. They give a contrasting and diffuse picture of what inclusion is and about how inclusion is practiced. This article discusses two different ways of researching inclusive education and defining inclusion to be found in the Norwegian research literature. It is argued that by adopting either just a macro-orientation, studying the school structures, or only a micro-orientation, studying what selected teachers do in class, obscures other important issues that determine the quality of what goes on in school and that have to be addressed for inclusion to be operative.